Efficacy of freeze-chilled storage combined with tea polyphenol for controlling melanosis, quality deterioration, and spoilage bacterial growth of Pacific white shrimp (Litopenaeus vannamei). (15th February 2022) - Li, Yan; Lei, Yutian; Tan, Yuqing; Zhang, Jingbin; Hong, Hui; Luo, Yongkang
Graphical abstract: Freeze-chilling deteriorated the quality of Pacific white shrimp. Coordinating with tea polyphenols (TP) remarkably improved the quality of freeze-chilled Pacific white shrimp. Highlights: Quality attributes and bacterial growth of freeze-chilled shrimp were analyzed. Freeze-chilled storage deteriorated the quality and altered microbiota of shrimp. Pseudoalteromonas and Photobacterium were inhibited by freeze-chilled storage. Tea polyphenols retarded quality deterioration of freeze-chilled shrimp. Abstract: This study aimed to investigate melanosis, quality attributes, and bacterial growth of freeze-chilled Pacific white shrimp ( Litopenaeus vannamei ) during 6 days of chilled storage, as well as the preservative effects of tea polyphenol on shrimp. The results showed that freeze-chilled storage retarded the growth of bacteria and the accumulation of putrescine in shrimp. The growth of spoilage bacteria Photobacterium and Shewanella were inhibited. However, freeze-chilled storage aggravated melanosis and lipid oxidation. The total volatile basic nitrogen (TVB-N) slightly accumulated in the thawed shrimp. The incorporation of tea polyphenol preserved freeze-chilled shrimp. Melanosis and lipid oxidation of shrimp were alleviated. The accumulation of biogenic amines, TVB-N, hypoxanthine riboside, and hypoxanthine were retarded. Meanwhile, the growth of spoilage bacteria Pseudoalteromonas, Photobacterium, Psychrobacter, and Carnobacterium were inhibited. Based on sensory analysis, the shelf-life of chilled, freeze-chilled, and freeze-chilled tea polyphenol shrimp were 4 days, 3 days, and 6 days, respectively.